Manfaat Tanaman mangrove terhadap Pengobatan Diabetes - Shina Megaputri Gandaninata Yushan (Yayasan Pendidikan Medika Indonesia, 2021)
Diabetes is a serious chronic disease that occurs when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin. The increasing prevalence of Type 2 Diabetes Mellitus from year to year and Diabetes Mellitus treatment which must be consumed every day have caused many side effects. Some people try to use herbs to dicrease blood glucose. Mangrove extracts are believed to dicrease blood sugar because they contain alkanoids, flavonoids, saponins, and tannins. Some studies also say that consuming large amounts of mangrove extracts can dicrease blood sugar compared to small amounts.